Retracted : Research on psychological satisfaction of education work and learning of literary works - Wang, Yuanyuan (HTS teologiese studies, 2023)
The findings of this article reveal that the development of the independent learning model in the American literature curriculum positively impacts teachers’ job psychological satisfaction. This study highlights the contribution of autonomous learning mode in empowering students’ subjective status and enhancing their initiative, consequently reducing teachers’ psychological pressure and improving their overall satisfaction with their work.Contribution: The results of this study hold implications for scholars in the field, particularly those engaged in practical theology and religious educational studies.Reason for retraction: The article ‘Research on psychological satisfaction of education work and learning of literary works’ by Yuanyuan Wang has been retracted by AOSIS, as publisher, following an investigation undertaken by the publisher. This investigation has uncovered evidence of systematic manipulation of the publication and peer-review process. We cannot, therefore, vouch for the reliability or integrity of this article. Please note that this notice is intended solely to alert readers that the peer-review process of this article has been compromised. AOSIS regret that the usual quality checks did not identify these issues before publication and has since put additional measures in place to safeguard research integrity. The corresponding author, as the representative of all authors, has been given the opportunity to register their agreement or disagreement with this retraction. We have kept a record of any response received.